Defining the next generation home for Singaporeans. - Chang, Hui Yiing. (2008)
This study is about the future home in Singapore.This project explores the structure, social and technology trends expected. Our vision of the future home in Singapore is a smaller house with space saving and aesthetically appealing furniture and fittings, containing appliances and electronic devices which enable e-lifestyle.